Review of modern instrumentation for magnetic measurements at high pressure and low temperature - Wang, X.; Kamenev, K.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
High-pressure magnetic susceptibility experiments can provide insights into the changes in magnetic behavior and electric properties which can accompany extreme compressions of material. Instrumentation plays an important role in the experimental work in this field since 1990s. Here we present a comprehensive review of the high-pressure instrumentation development for magnetic measurement from the engineering perspective in the last 20 years. Suitable nonmagnetic materials for high pressure cell are introduced initially. Then we focus on the existing cells developed for magnetic property measurement system (MPMS®) SQUID magnetometer from Quantum Design (USA). Two categories of high pressure cells for this system are discussed in detail respectively. Some high pressure cells with built-in magnetic measurement system are also reviewed.